PHYSIOLOGICAL RESPONSES OF RABBITS TO PETROL-GENERATOR EXHAUST FUME EXPOSURE - O. A., Adika; G. O., Gabriel (Kashere Journal of Animal Science, 2025)
Dependence on petrol generators in developing countries exposes humans and animals to toxic exhaust emissions. this study was carried out at federal university Oye- Ekiti teaching and research farm of the department of animal production and health. This study assessed the effects of petrol-generator exhaust fumes on haematological and serum biochemical parameters of rabbits. Twenty (20) Rabbits were randomly assigned into four treatment groups (T1, T2, T3 and T4): control T1(no exposure) and treatment groups T2, T3 and T4 were exposed for 2, 4, or 6 hours daily respectively. The experiment lasted for 6weeks, at the end of the research, Blood samples were collected for haematological (MCHC, haemoglobin, PCV, leukocyte differentials) and serum biochemical (ALT, AST, ALP, urea, creatinine) analyses. Data were analyzed using one-way ANOVA at (p<0.05). Haematological indices showed some level of changes in haemoglobin and MCHC, with a decrease after 6-hour exposure, while PCV increased significantly compared with control group. Leukocyte counts indicated stress-related neutrophilia and lymphocytosis. serum Biochemical analysis revealed elevated ALT, AST, and ALP activities in 2- and 4-hour treatment groups, followed by a decrease at 6 hours, suggesting hepatocellular stress. Serum urea and creatinine were significantly increased in exposed treatment groups, indicating impede renal function. Exposure to petrol-generator exhaust fumes adversely affect haematological and serum biochemical indices of rabbits, reflecting hypoxia, inflammatory responses, hepatotoxicity, and nephrotoxicity. These findings highlight potential public health risks associated with chronic generator use and stress the need for safer energy alternatives and improved ventilation practices.